Two- and three-dimensional ray tracing applied to the land mobile satellite (LMS) propagation channel. - Dottling, M. (IEEE Antennas & propagation magazine.)
This work examines the application of ray-tracing propagation models to system simulations for satellite mobile communications. A two-dimensional (2D) and a three-dimensional (3D) algorithm are outlined and compared using canonical propagation problems. Additional comparisons of both models with measurement campaigns are performed. The results show that two-dimensional models are suited for coverage and network planning. For system-design studies, however, three-dimensional ray tracing is mandatory. The novel three-dimensional ray-tracing model is able to predict time series of power delay profiles, Doppler and polarimetric information with high precision. It includes the time-variant correlation between the propagation channels of all visible satellites of an arbitrary satellite constellation. It therefore proves to be especially suited for system investigation of future LMS communication and navigation systems